Neuronal number and somal volume in calbindin-expressing neurons of the marmoset dorsal lateral geniculate nucleus are preserved during aging - Nelyane N. M. Santana; Maria M. O. da Silva; Eryck H. A. Silva; Sâmarah F. dos Santos; Lyzandro L.F. Bezerra; Wellydo K. M. Escarião; Gabriel A. M. Vasiljevic; Felipe P. Fiuza; Jeferson S. Cavalcante; Rovena Clara Engelberth (PLoS ONE, 2025)
Compelling evidence links age-related brain dysfunction and neurodegenerative processes to persistent disruptions in intracellular calcium (Ca2+) signaling, a central hypothesis in the Ca2+ theory of aging. Calbindin (CB), a classical Ca2+ buffer, has been implicated in region-specific susceptibility to aging-related effects. Specifically, CB-immunopositive (CB+) neurons have demonstrated an age-dependent decline in neuronal number across various cortical and subcortical regions. However, it remains unclear whether this decrease occur in the dorsal lateral geniculate nucleus (DLG), a crucial relay and modulatory center for visual processing. Additionally, the potential impact of aging on the cellular volume of CB+ neurons in the DLG has not been fully elucidated, albeit an age-dependent neuronal hypertrophy of this region has been reported. To address these questions, we investigated CB+ neurons in the DLG of six marmosets (Callithrix jacchus), aged between 29–143 months. Using design-based stereological techniques, we estimated the total number and somal volume of CB+ neurons in DLG layers. Our results revealed no signs of CB+ neuronal number loss and somal volumetric changes in aged DLG, particularly within the koniocellular layers, a stratum that primarily expresses CB and play a critical role in blue/yellow color vision. Altogether, our findings suggest a preserved neuronal number and cellular volume of the CB+ population during aging process in the marmoset DLG. Moreover, they provide a valuable basis for future investigations into the neuroprotective role of CB in visual processing during aging and open avenues for strategies designed to preserve vulnerable neuronal populations in age-related neurodegenerative conditions.